Lenvatinib Plus PD-1 Inhibitors as First-Line Treatment in Patients With Unresectable Biliary Tract Cancer: A Single-Arm, Open-Label, Phase II Study - Zhang, Qiyi; Liu, Xingyu; Wei, Shumei; Zhang, Lufei; Tian, Yang; Gao, Zhenzhen; Jin, Ming; Yan, Sheng (Frontiers in Oncology, 2021)
Objective: We investigated lenvatinib plus programmed cell death-1 (PD-1) inhibitors as a first-line treatment for initially unresectable biliary tract cancer (BTC). Methods: In this Phase II study, adults with initially unresectable BTC received lenvatinib (body weight ≥60 kg, 12 mg; <60 kg, 8 mg) daily and PD-1 inhibitors (pembrolizumab/ tislelizumab/ sintilimab/ camrelizumab 200 mg or toripalimab 240 mg) every 3 weeks. Primary endpoints were objective response rate (ORR) and safety. Secondary endpoints included surgical conversion rate, disease control rate (DCR), event-free survival (EFS), overall survival (OS) and tumor biomarkers. Results: Among 38 enrolled patients, the ORR was 42.1% and the DCR was 71.1%. Thirteen (34.2%) patients achieved downstaging and underwent surgery, of whom six (46.2%) achieved a major pathologic response (n=2) or partial pathologic response (n=4) in the primary tumor. In total, 84.2% of patients experienced ≥1 treatment-related adverse event (TRAE), 34.2% experienced a Grade ≥3 TRAE and no treatment-related deaths occurred. After a median follow-up of 13.7 months the median EFS was 8.0 months (95% CI: 4.6–11.4) and the median OS was 17.7 months (95% CI: not estimable). Conclusions: Lenvatinib plus PD-1 inhibitors showed promising anti-tumor efficacy in patients with initially unresectable BTC and was generally well tolerated.